2022
DOI: 10.2196/36181
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of COVID-19 Lockdown Restrictions With Longer-Term Activity Levels of Working Adults With Type 2 Diabetes: Cohort Study

Abstract: Background Lockdown restrictions reduce COVID-19 community transmission; however, they may pose challenges for noncommunicable disease management. A 112-day hard lockdown in Victoria, Australia (commencing March 23, 2020) coincided with an intervention trial of reducing and breaking up sitting time in desk workers with type 2 diabetes who were using a provided consumer-grade activity tracker (Fitbit). Objective This study aims to compare continuously re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Another contributing factor to the increase in revascularisations during the pandemic is a general decline in patient health during the pandemic. This has been reported by several studies and a systematic review which found reduced physical activity and increased sedentary behaviours in several populations of adults with a variety of medical conditions during lockdowns [17–19]. Additionally, reduced physical activity and increased sedentary behaviours are associated with poor glycaemic control which overtime likely contributed to deterioration of PAD further in diabetic patients [20, 21].…”
Section: Discussionmentioning
confidence: 81%
“…Another contributing factor to the increase in revascularisations during the pandemic is a general decline in patient health during the pandemic. This has been reported by several studies and a systematic review which found reduced physical activity and increased sedentary behaviours in several populations of adults with a variety of medical conditions during lockdowns [17–19]. Additionally, reduced physical activity and increased sedentary behaviours are associated with poor glycaemic control which overtime likely contributed to deterioration of PAD further in diabetic patients [20, 21].…”
Section: Discussionmentioning
confidence: 81%
“…Adding to the considerations for measurement selection for researchers is the rapid increase in the technology available for measuring activity [ 33 ]. Technology-based methods of smartphone accelerometers [ 34 ], Fitbits [ 35 ] and research-grade accelerometers [ 36 ] were used to measure physical activity and sedentary behaviour during the pandemic and can be used across work and home environments. These provide higher accuracy than self-reports, but minimal information regarding context, which is necessary to target setting-specific changes in active and sedentary behaviour.…”
mentioning
confidence: 99%